2022
DOI: 10.1002/lno.12204
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional response of a coccolithophore to changing pH and temperature

Abstract: Coccolithophores are a calcifying unicellular phytoplankton group that are at the base of the marine food web, and their lipid content provides a source of energy to consumers. Coccolithophores are vulnerable to ocean acidification and warming, therefore it is critical to establish the effects of climate change on these significant marine primary producers, and determine potential consequences that these changes can have on their consumers. Here, we quantified the impact of changes in pH and temperature on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Although, carbohydrates are the major energy storage, Fernandez et al (1994) reported that coccolithophores under stress save more lipids as their metabolic energy reserves and utilize them as alternative carbon sources for cellular processes including protein synthesis. It is due to carbon components under OW and OA condition in coccolithophore shunt to increases more lipid which act as primary source of energy for energy utilization and cellular process (Johnson et al, 2022). Our data show larger lipid accumulation than that of carbohydrate when cells are exposed to the HTHC condition (Figure 3A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Although, carbohydrates are the major energy storage, Fernandez et al (1994) reported that coccolithophores under stress save more lipids as their metabolic energy reserves and utilize them as alternative carbon sources for cellular processes including protein synthesis. It is due to carbon components under OW and OA condition in coccolithophore shunt to increases more lipid which act as primary source of energy for energy utilization and cellular process (Johnson et al, 2022). Our data show larger lipid accumulation than that of carbohydrate when cells are exposed to the HTHC condition (Figure 3A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Detrimental effects are caused by the rapid and extreme sea surface warming and the synergy with OA (Milner et al, 2016;D'Amario et al, 2017;D'Amario et al, 2020). Laboratory experiments (Fiorini et al, 2011;Milner et al, 2016;Johnson et al, 2022), long-term sediment trap series and observations in naturally high CO 2 concentration sites (CO 2 vents, off Vulcano island, Italy, Tyrrhenian sub-basin) show negative impacts of OA on coccolith weight and biodiversity (Triantaphyllou et al, 2010;Meier et al, 2014;Ziveri et al, 2014). Another study in natural CO 2 gradient sites (CO 2 vents, Aegean sub-basin) had reported increased biodiversity with high CO 2 conditions (Triantaphyllou et al, 2018).…”
Section: Calcifying Phytoplankton: Coccolithophoresmentioning
confidence: 97%
“…High sensitivity to temperature may also expand the poleward extent of coccolithophore growth, as has been observed in the Barents Sea (Smyth et al, 2004). Growth may increase at substantially higher temperatures (K. S. Johnson, Riser, et al, 2022;R. Johnson, Langer, et al, 2022), and evolutionary adaptation of coccolithophores may increase their tolerance to higher temperatures (Schlüter et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…High sensitivity to temperature may also expand the poleward extent of coccolithophore growth, as has been observed in the Barents Sea (Smyth et al., 2004). Growth may increase at substantially higher temperatures (K. S. Johnson, Riser, et al., 2022; R. Johnson, Langer, et al., 2022), and evolutionary adaptation of coccolithophores may increase their tolerance to higher temperatures (Schlüter et al., 2014). Temperature‐driven increases in coccolithophore growth may not necessarily drive increased surface PIC, however, as calcification may decline under higher CO 2 (Freeman & Lovenduski, 2015; Krumhardt et al., 2019) and temperatures (Rosas‐Navarro et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation